Factors Associating with Alcohol Consumption Behavior Among Drunk Drivers in Bangkok Metropolis - ตันติธรรม นงนุช (Disease Control Journal, 2007)
This cross-sectional survey study was aimed to investigate alcohol consumption behavior and identify factors associated with alcohol consumption among drunk drivers in Bangkok Metropolis. The 390 subjects were selected by systemic sampling method from drunk drivers who had been taken into custody of driving because having upper blood alcohol concentration limits of 0.5 g/dl. The data were collected by questionnaire on February 2006 and were analyzed for frequency, percentage, mean, standard deviation and Pearson’s Product Moment Correlation Coefficient. The results showed that 40.3% of the samples had alcohol consumption 2-3 times per week while 5.6 % had daily. The predisposing factors that had significantly positive association with alcohol consumption behavior were attitudes toward impaired drivers and perceived risk of traffic accident from the drunk drivers. The enabling factors that had significantly positive association with alcohol consumption behavior were place of beverage drinking. The reinforcing factors that had significantly positive association with alcohol consumption behavior were the influence of information received from media and supports to alcohol consumption from the parents. In spite of drunk drivers known and perceived accidental and violent risk, they still practiced drink and drive because they thaught that they had less chance of being arrested as alcoholic checkpoints to assess their level of alcohol consumption had been irregularly set up, only during major festivals and celebrations. The most important was that part of sample group thaught that they had enough ability to drive if they had consciousness regardless of having drink and reached upper blood alcohol concentration limit (0.05 mg%). In fact their family did not complain or blame them and sometimes invited to enjoy drinking. According to Thai traditional, most of party meetings always contained alcoholic drink with either advertisements or sponsors. Thus resolving this problem, the programme should use several preventive measures for reducing drunk drive such as enforcing alcohol laws by random breath-testing and adequate alcoholic checkpoints with consistency and continuity, uncompromised punitive measures, wide spread information, education and communication campaigns about risk factors, in particular, the effect of alcohol abuse. All of these measures should be raised to enlarge safety-awareness and improving their behavior later.